Initial horticultural performance of nine ‘Persian’ lime selections grafted onto Swingle citrumelo - Magno Guimarães Santos (Scientia Agricola, 2016)
ABSTRACT ‘Persian’ lime (PL) [Citrus latifolia (Yu. Tanaka) Tanaka] is an important species both for domestic fresh fruit consumption in Brazil as well as the export market, since the country is one of the largest producers in the world despite the fact that, in commercial plantations, it is still not uncommon to find trees with low productivity and high plant vigor of unknown origin. Selections of Persian lime ‘CNPMF–2000’, ‘CNPMF–2001’, ‘CNPMF–01’, ‘CNPMF–02’, ‘IAC–5’, ‘IAC–5.1’, ‘Bearss’, ‘Persian–58’, and ‘5059’, were therefore grafted onto Swingle citrumelo [C. paradisi Macfad. cv. Duncan × Poncirus trifoliata (L.) Raf.] rootstocks and evaluated in Cruz das Almas, Bahia, Brazil in a field experiment conducted in a completely randomized block design with five replications and two trees per plot. The biometric attributes (canopy height, diameter and volume), yield parameters (yield during the off-season harvest period, yield per plant, production efficiency), and fruit quality traits, were evaluated. The ‘CNPMF–2001’, ‘CNPMF–01’, ‘CNPMF–02’, ‘IAC–5’, and ‘Bearss’ selections had 5-11 % shorter trees than the other cultivars. ‘CNPMF–01’, ‘CNPMF–02’, ‘Persian–58’, and ‘5059’ presented higher yield efficiency values, between 3.1-3.4 kg m−3, and higher yield levels during the off-season harvest periods. The ‘Bearss’, ‘Persian–58’, ‘CNPMF–2000’, ‘IAC–5.1’ and ‘5059’ selections had more acid fruits and the latter three, smaller fruits. Based on their horticultural performance up to eight years of age, ‘CNPMF–01’, ‘CNPMF–02’, ‘Persian–58’ and ‘5059’ selections were the most promising varieties of Persian lime.